Biographical viewpoints in museology: the challenges of intersubjectivity (Cadernos de Sociomuseologia, 2015)
In this paper, we propose a reflection on the use of biographical objects in museum studies, as a process of production and inclusion of knowledge in society. The theoretical renewal of sociomuseological approach, a process that has been conducted by MINOM and several universities, is founded on the premises of theories adequacy of museum structures and processes to the rhythms and needs of contemporary societies. Globalization has been influencing the opening of organizations and processes through which they are involved in an intimate relationship with the communities and territories that become integrated in their diversity. In this transformative movement emerge new museum objects that trigger a need to develop and clarify relationships, notions and concepts to realize these processes. Through these new objects ripping new perspectives for research and action that reactualized methodologies and renew the action of museum and heritage organizations. These new narratives allow adaptation and adjustment of museological processes to social processes.Keywords: Sociomuseology, Intersubjectivity, Oral Narratives, Critical Museology, Social Change